2017
DOI: 10.3892/ol.2017.5557
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Ras/Raf/MEK/ERK pathway in hepatocellular carcinoma

Abstract: Abstract. Although the biological basis of hepatocellular carcinoma (HCC) remains unclear, effective treatments and improvement of the survival rate remain worthwhile research goals. Abnormal protein signaling pathways contributing to uncontrolled cell proliferation, differentiation, survival and apoptosis are biomarkers of the carcinogenic process. Certain mutated components or overexpression of the rat sarcoma virus (Ras)/rapidly accelerated fibrosarcoma (Raf)/mitogen-activated protein kinase kinase (MEK)/ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
126
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(132 citation statements)
references
References 71 publications
4
126
0
2
Order By: Relevance
“…These findings suggest that activation of ERK and its upstream signaling cascades might be involved in the down‐regulation of CIC protein levels. Many studies have demonstrated that the RAS/RAF/MEK/ERK signaling pathway is associated with HCC pathogenesis . Levels of total or phosphorylated ERK are often higher in HCC cells than in normal liver cells .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These findings suggest that activation of ERK and its upstream signaling cascades might be involved in the down‐regulation of CIC protein levels. Many studies have demonstrated that the RAS/RAF/MEK/ERK signaling pathway is associated with HCC pathogenesis . Levels of total or phosphorylated ERK are often higher in HCC cells than in normal liver cells .…”
Section: Discussionmentioning
confidence: 77%
“…Many studies have demonstrated that the RAS/RAF/MEK/ ERK signaling pathway is associated with HCC pathogenesis. (46,47) Levels of total or phosphorylated ERK are often higher in HCC cells than in normal liver cells. (48,49) Moreover, it was reported that ERK is mainly found in the nucleus of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…These signaling pathways are often dysregulated and hyperactivated in HCC and promote cancer cell metabolic adaptation, proliferation, and tumor growth. (1,6,7,33,(41)(42)(43) Nqo1-KD in liver cancer cells blunted activation of both the PI3K/Akt and MAPK/ERK signaling pathways, indicating that Nqo1 functions upstream and is required for the activation of these pathways. How does Nqo1 regulate these two pathways simultaneously?…”
Section: Discussionmentioning
confidence: 99%
“…Most significantly, we discovered that Nqo1 is required for the activation of two major pro‐oncogenic signaling pathways in liver cancer cells: PI3K/Akt and MAPK/ERK. These signaling pathways are often dysregulated and hyperactivated in HCC and promote cancer cell metabolic adaptation, proliferation, and tumor growth . Nqo1‐KD in liver cancer cells blunted activation of both the PI3K/Akt and MAPK/ERK signaling pathways, indicating that Nqo1 functions upstream and is required for the activation of these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the possible target mechanism involved in the anticancer activities of ACE‐63, we used a phosphokinase array. Numerous studies have indicated that the PI3K/AKT and RAF/MAPK pathways are dysregulated in a large proportion of human HCC, and this signaling was associated with aggressive tumor phenotype, poor prognosis, and inhibition of the apoptotic response in human HCC (Matter, Decaens, Andersen, & Thorgeirsson, ; Minguez, Tovar, Chiang, et al, ; Will, Qin, Toy, et al, ; Yang, ). Indeed, we observed that the PI3K/AKT and RAF/MAPK pathways were highly activated in HepG2 cells using a phosphokinase array.…”
Section: Discussionmentioning
confidence: 99%